2005
DOI: 10.1038/nmat1414
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the conductance of single-walled carbon nanotubes by ion irradiation in the Anderson localization regime

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: El acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription Tuning the conductance of single walled carbon nanotubes by ion irradiation in the Anderson localization regimeC. Gómez-Navarro 1 , P.J. Carbon nanotubes 1,2 are a good realization of one-dimensional crystals where basic science and potential nanodevice applications … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
321
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(345 citation statements)
references
References 29 publications
19
321
0
4
Order By: Relevance
“…10 This theory has been used to explain exponential length dependences of the resistance measured in nanotubes. [26][27][28] SL occurs when the phase-coherence length L becomes longer than the localization length L loc . This is equivalent to when the width of the coherent states, បv F / L , becomes smaller than the energy separation between the localized states.…”
Section: Discussionmentioning
confidence: 99%
“…10 This theory has been used to explain exponential length dependences of the resistance measured in nanotubes. [26][27][28] SL occurs when the phase-coherence length L becomes longer than the localization length L loc . This is equivalent to when the width of the coherent states, បv F / L , becomes smaller than the energy separation between the localized states.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of double vacancies in irradiated nanotubes was corroborated by recent experiments on the dependence of the SWNT conductance on Ar ion irradiation dose. 32 The other factor which affects the evolution of nanotubes under irradiation is the diffusivity of interstitials. As we recently showed, 17 carbon atoms can easily migrate via the inner hollow.…”
Section: Interaction Of the Electron Beam With Defected Nanotubesmentioning
confidence: 99%
“…[12][13][14] More insight into the effect of individual defects on the electronic properties was obtained from low-dose irradiation of SWNTs with 120 eV Ar + ions. 15 It was shown that ion-irradiation-induced double vacancies ͑DVs͒, in comparison to single vacancies ͑SVs͒, strongly reduce the conductivity of metallic tubes. The effects of irradiation in more complicated systems, such as SWNT bundles 16 and films, 17,18 have also been studied and interesting effects such as an increase in the conductance after moderate irradiation dose have been reported.…”
Section: Introductionmentioning
confidence: 99%